Design and Development of an Automatic Asem Keping Drying System Using Infrared Heater Based on Fuzzy Logic - Syahrul Ramadan; Rini Puji Astutik (Lembaga Pengembangan Kinerja Dosen, 2025)
The drying process of Asam Keping (Garcinia atroviridis) is a crucial stage in food processing that significantly affects the final product quality. Conventional drying methods that rely on sunlight have several limitations, such as dependency on weather conditions, extended drying time, and inconsistent results. This study aims to design a drying system for Asam Keping controlled using the fuzzy logic method. The research is expected to improve energy efficiency, accelerate the drying process, and maintain the quality of the dried product. The drying system is designed using an infrared heater as the heat source, temperature and humidity sensors to monitor environmental conditions, and a microcontroller as the main controller. The fuzzy logic method is implemented to adjust the drying temperature and duration adaptively based on environmental parameters and the desired dryness level. The results of this study are expected to reduce drying time by approximately 50% compared to conventional methods. Additionally, the dried Asam Keping is expected to achieve the desired moisture content while preserving its color and texture quality. The analysis of this study concludes that an infrared heater-based drying system utilizing fuzzy logic can be an effective solution for the Asam Keping drying process in terms of time efficiency and product quality.